2021
DOI: 10.1371/journal.pone.0243355
|View full text |Cite|
|
Sign up to set email alerts
|

The determinant factors for the adoption of CRM in the Palestinian SMEs: The moderating effect of firm size

Abstract: CRM adoption can provide innumerable benefits to the SMEs performance, including solving customer problems in a timely manner, enhancing customer satisfaction by appointing an expert to solve issues and queries, and the like. This study aims to examine the moderating effects of the firm size in the adoption of CRM in the Palestinian SMEs. A quantitative approach was used to investigate the relationships between the variables, which are compatibility, IT infrastructure, complexity, relative advantage, security,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 98 publications
0
5
1
Order By: Relevance
“…Second, similar to the moderation effect of gender, the effect of firm size shows no interaction effect on performance expectancy, effort expectancy, social influence, perceived credibility or behavioural intention to use, nor on behavioural intention to actually use. This finding is contrary to the studies of Salah et al (2021) and Wang et al (2018) but consistent with that of Pan et al (2022). The reason behind the inconsistency might be that the majority of respondents represented medium and large firms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Second, similar to the moderation effect of gender, the effect of firm size shows no interaction effect on performance expectancy, effort expectancy, social influence, perceived credibility or behavioural intention to use, nor on behavioural intention to actually use. This finding is contrary to the studies of Salah et al (2021) and Wang et al (2018) but consistent with that of Pan et al (2022). The reason behind the inconsistency might be that the majority of respondents represented medium and large firms.…”
Section: Discussioncontrasting
confidence: 99%
“…This leads to significant investment in technological advancement and innovation, whereas small firms suffer from a lack of resources (Ahmadi et al, 2018). Salah et al (2021) conducted a study on SMEs operating in Palestine to identify the dominant factors affecting customer relationship management with the moderation influence of firm size; they reveal that it significantly influenced the adoption of customer relationship management. On the contrary, the study of Alhammadi et al (2015) showed that firm size had no significant impact on cloud computing adoption in Saudi Arabia.…”
Section: Firm Size As Moderatormentioning
confidence: 99%
“…The importance of factors that can influence innovation in family firms by several specific control variables (firm scale, firm age, the rate of profit rate, the revenue growth rate, the proportion of family shareholding). The firm scale is measured by the number of employees, because the firm scale is closely related to the level of knowledge acquisition, and which could influence investment in innovation [95]. The firm age is calculated based on the difference between the year (2009) in which the survey was conducted and the year in which the firm was founded.…”
Section: Moderating Variablesmentioning
confidence: 99%
“…The whole business is combined by the system and streamlined in a single operational platform to bring about long-term efficient business activities. ERP portfolio for private sector businesses comes in various types and sizes, covering a huge variety of industry-focused functions reinforced through convergent billing, receivables supervision and customer relationship management (CRM) [31]. ERP also combines front-line solutions to address labour market requirements and industry-centred and business expertise future needs, and to assist in market development and business survival [21].…”
Section: Introductionmentioning
confidence: 99%